2007
DOI: 10.3844/ajavsp.2007.108.113
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Digestibility and Gas Production of Some Tropical Feeds Used in Ruminant Diets Estimated by the in vivo and in vitro Gas Production Techniques

Abstract: Some feedstuffs which used in ruminants diet (corn grain, soybean meal, wheat bran and alfalfa) were analyzed for chemical composition, apparent in vivo nutrient digestibility, in vitro fermentation gas production and metabolizable energy. Chemical composition of test feeds differed in nutrient contents. Initially apparent in vivo digestibility of alfalfa nutrients were obtained then digestibility of nutrients for the other test feeds were determined by difference method, using 16 Ghezel mature rams (mean weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 27 publications
0
9
1
2
Order By: Relevance
“…Many native browse species have been undervalued because of insufficient knowledge of their feeding value and for their often high content of tannins, which may be detrimental to animal performance (Min et al, 2003). The nutritive value of feeds utilized in ruminant nutrition are commonly estimated by the concentrations of chemical components, and the rates and extents of nutrient digestion (Hamid et al, 2007). The in vitro gas production procedure has become a useful tool to study potential rumen degradation of ruminant feeds (Getachew et al, 2002;Salem et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many native browse species have been undervalued because of insufficient knowledge of their feeding value and for their often high content of tannins, which may be detrimental to animal performance (Min et al, 2003). The nutritive value of feeds utilized in ruminant nutrition are commonly estimated by the concentrations of chemical components, and the rates and extents of nutrient digestion (Hamid et al, 2007). The in vitro gas production procedure has become a useful tool to study potential rumen degradation of ruminant feeds (Getachew et al, 2002;Salem et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that species with high cell wall and lignin contents showed an increase of lag time (HAMID et al, 2007;CHANG et al, 2007), and a decrease in the rate of gas production (C parameter) and in vitro DMD and OMD (SANDOVAL-CASTRO et al, 2005), which is in accordance with the findings of the present study, in which bean silage showed the highest values of ADL associated with the lowest values of DMD and OMD; also, ryegrass silage showed the lowest lag time associated with its significant lower level (P<0.001) of ADL. CHANG et al (2001) suggested that the current fiber of the diets based on the total NDF content can hardly predict the requirements for dietary fiber in rabbits due to the complex chemical composition of the total dietary fiber and its multiple interactions with the microbial caecal ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Studi in vitro perlu dilakukan untuk mengevaluasi penggunaan tepung daun nangka untuk meningkatkan efektifitas penggunaan hijauan berupa daun M. oleifera dan jerami V. radiata. Metode in vitro gas test digunakan untuk menguji pakan tunggal dan memiliki korelasi yang tinggi dengan uji in vivo (Menke et al, 1979;Getachew et al, 2000;Hamid et al, 2007). Tujuan dari studi yang dilakukan adalah untuk mengevaluasi penambahan tepung daun nangka terhadap proses fermentasi dan degradasi daun M. oleifera dan jerami V. radiata.…”
Section: Pendahuluanunclassified